In vitro biofilm formation by Escherichia Coli and its sensitivity to chemical disinfectants at different incubation temperatures and times - Anas Muazu
Biofilms are aggregate of microbial cells enclosed in an extracellular polymeric substance and attached to surfaces. Biofilm formation on implant medical devices, food contact surfaces and its resistance to chemical disinfectants posed a serious challene to the public health, resulting in multiple infections. The aim of this work was to study the development of Escherichia coli biofilm on glass, stainless steel (SS), wood and Polystyrene Tissue Culture plates (TCP) at various incubation temperatures and time and to assess the efficacy of hydrogen peroxide (HP), acetic acid (AA), sodium hypochlorite (SH), mixture of AA and SH against its biofilm. 200 µL of 10'8 cell suspension of E. coli ATCC 29922 was inoculated on the surfaces and incubated at 10, 27 and 37oC for 24, 48 and 72 hours to allow biofilm development. At each hour of incubation stated above, the number of bacterial cells developed was enumerated. The effects of disinfectants were tested against biofilm which developed after 168 hours. The surfaces were exposed to the disinfectants, incubated at room temperature for 10 minutes followed by deactivation for 5 minutes. Viable cells that survived bactericidal effect were enumerated by agar plating and incubated at 370C for 24 hours. Developed colonies were converted into colony forming unit per mL (CFU/mL). From the results it was found that E. coli biofilm developed higher on glass with a count of 1.40 x 109 CFU/mL followed by SS (1.22 x 109 CFU/mL), then wood (8.10 x 108 CFU/mL), while least biofilm was developed on TC plate (1.50 x 108 CFU/mL). After treatment with disinfectants, HP had the highest bactericidal effect with 1.94 log reduction (LR) followed by AA (1.71 LR) while SH had the least efficacy with 1.53 LR. The mixture of AA and SH produced bactericidal effect of 1.77 LR which was greater than their individual effects at 37oC, less than that of AA (1.04 LR) at 27oC, greater than that of SH (1.03 LR) at 10oC. Thus from this case study, it can be concluded that in addition to glass, stainless steel and TC plates, E. coli biofilm also developed on wood. The effect of disinfectants demonstrated that HP is a good disinfectant against E. coli biofilm followed by AA and SH. The combination of AA and SH does not produce a far better bactericidal effect than their individual actions.